Looking East : Indian wisdom for modern management - Mukherjee, Sanjoy (Oxford ; New York : Peter Lang Publishing, 2022)
"The book is an exploration of the relevance of Indian classical wisdom in reorienting modern management. It highlights the urgent need for facilitating an internally-directed spiritual dimension to business management, including management education as an alternative to instrumental rationality and extreme materialistic orientation in today's profit-driven business world. The book presents spiritualty or enlightened consciousness as the essence of a transformational or rather transcendental leader to improve the quality of work-life within by creating a humane and enduring organizational culture. It does this by drawing upon inspiration from modern Indian leaders like Rabindranath Tagore and Swami Vivekananda. It also offers insights into alternative sources and methods of learning in management and life from ancient Indian wisdom and selected European literature to infuse creativity, joy, meaning and purpose into work and life. The book facilitates East-West dialogue on value-based holistic management in a globalized business scenario. In the modern business paradigm dominated by western management principles and practices, the book attempts to offer an Indian model of management founded on spirituality, human values and sustainability to deal with the alarming crises in a pandemic- stricken world by suggesting alternative ways of thinking and living for a sane, happy and sustainable future for both planet and people"--
Includes bibliographical references and index.
Keywords: Management -- India; Management -- Religious aspects; Management -- Environmental aspects; Business ethics -- India; Corporate culture -- India